2022
DOI: 10.1101/2022.10.07.511245
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Farnesoid X Receptor suppresses lipid peroxidation and ferroptosis

Abstract: Objective: Ferroptosis is a regulated cell death modality that occurs upon iron-dependent lipid peroxidation. The recent decade of research has uncovered many regulators driving ferroptosis as well as cellular gatekeepers preventing ferroptosis. Yet, many processes and networks remain to be elucidated. Methods and results: In this study, we performed a chemical screen using small molecules with known mode of action and identified two agonists (Turofexorate and Fexaramine) of the nuclear receptor Farnesoid X R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Apart from the fatty acid metabolic processes mentioned earlier and implicated in ferroptosis regulation, bile acid metabolism also connects to ferroptosis. For example, Tschuck et al have shown that the activation of the nuclear receptor Farnesoid X receptor, triggered by bile acids, leads to the upregulation of pivotal genes, namely GPX4, FSP1, and ACSL3, that curtail ferroptosis [76] . In essence, the network of lipid metabolism plays a pivotal role in both the initiation and modulation of lipid peroxidation during ferroptosis [76] .…”
Section: Lipid Peroxidationmentioning
confidence: 99%
“…Apart from the fatty acid metabolic processes mentioned earlier and implicated in ferroptosis regulation, bile acid metabolism also connects to ferroptosis. For example, Tschuck et al have shown that the activation of the nuclear receptor Farnesoid X receptor, triggered by bile acids, leads to the upregulation of pivotal genes, namely GPX4, FSP1, and ACSL3, that curtail ferroptosis [76] . In essence, the network of lipid metabolism plays a pivotal role in both the initiation and modulation of lipid peroxidation during ferroptosis [76] .…”
Section: Lipid Peroxidationmentioning
confidence: 99%
“…Spheroids were cultured according to the protocol previously described 15 . In brief, HT-1080 were seeded into 96-well round bottom microplates (CellCarrier Spheroid ULA, PerkinElmer) with a density of 2,000 cells per well.…”
Section: Spheroid Formation Treatment and Imagingmentioning
confidence: 99%
“…Immunostaining of HT-1080 with anti-4-Hydroxynonenal-antibody (4-HNE, ab46545, Abcam) was performed as previously described 15 . In brief, ferroptotic cell death was induced via 300 nM RSL3 for 2 h and cells were co-treated with 20 µM ATRA or 2 µM ferrostatin-1.…”
Section: Antibody Staining and Flow Cytometrymentioning
confidence: 99%
See 2 more Smart Citations